Rāng Ratthathammanūn h̄æng Rātchaʻānāčhak Thai, Phutthasakkarāt --, phr̜̄omdūai rāingān kh̜̄ong Saphā Rāng Ratthathammanūn (Samnakngān Lēkhāthikān Saphā Rāng Ratthathammanūn, 1997)
Draft constitution of Thailand and report of constitutional drafting council.